Recycling of Demolished Concrete and Masonry. - Hansen, T. C. (Spon Press, 1992)
This new RILEM report contains state-of-the-art reviews on three topics: recycling of demolished concrete, recycling of masonry rubble and localized cutting by blasting of concrete. It has been compiled by an international RILEM Committee and draws on research and practical experience worldwide.